Mechanism of proline biosynthesis and role of proline metabolism enzymes under environmental stress in plants - Szepesi , Agnes; Szollosi, Reka
Proline (Pro)is a pivotal and multifunctional amino acid that can play a significant role not in just plant developmental processes but also in responses of biotic and abiotic stress. This chapter discusses the mechanism of Pro biosynthesis and the known and putative roles of Pro metabolism enzymes during environmental stress conditions in plants. We summarize our current knowledge about the role of Pro in some signaling pathways and interactions with phytohormones. Here, we highlight the latest findings in posttranscriptional modification of Pro metabolism enzymes supporting and emphasizing the role of Pro metabolism under adverse environmental stress conditions from excess heavy metals to drought and salt stress.
Keywords: ABIOTIC STRESS; BIOTIC STRESS; PROLINE DEHYDROGENASE; PROLINE METABOLISM; PROLINE